Haptically-Displayed Proprioceptive Feedback via Simultaneous Rotary Skin Stretch and Vibrotactile Stimulation - Lima, Bryanna; Hammond, Frank L. (IEEE RO-MAN, 2023)
The provision of proprioceptive feedback can be crucial to the use of wearable devices (prostheses) and teleoperated robots. This paper focuses on the development and evaluation of the wearable haptic feedback system capable of displaying proprioceptive information through rotary skin stretch and vibrotactile sensations. An experimental study was conducted to determine how well subjects can perceive skin stretch, applied to the posterior aspect of the upper arm by a rotating end effector, as proprioceptive feedback from a rotary input dial (potentiometer), and whether vibration can improve the accuracy of that proprioception. Results show that with skin stretch feedback, subjects could locate the angle of the input dial to within 5.48 degrees, compared to 5.82 degrees when participants had no feedback (used hand proprioception alone). When considering vibration alone and skin stretch with vibration, accuracy increased to 4.17 degrees and 4.25 degrees, respectively. Though proprioception of input dial angles improved with all forms of feedback, the time to subject determination of the angle increased by as much as 45%, from 4.4 sec to 6.4 sec.